Measures and Determinants of Urban Food Security: Evidence from Accra, Ghana - Tuholske, Cascade; Andam, Kwaw S.; Blekking, Jordan; Evans, Tom; Caylor, Kelly (International Food Policy Research Institute, 2018)
The urban population in Africa south of the Sahara (SSA) is expected to expand rapidly from 376 million people in 2015 to more than 1.25 billion people by 2050. Measuring and ensuring food security among urban households will become an increasingly pertinent task for development researchers and practitioners. In this paper we characterize food security among a sample of low- and middle-income residents of Accra, Ghana, using 2017 survey data. We find that households tend to purchase food from traditional markets, local stalls and kiosks, and street hawkers, and rarely from modern supermarkets. We characterize food security using three established metrics: the Household Food Insecurity Access Scale (HFIAS); the Household Food Insecurity Access Prevalence (HFIAP); and the Food Consumption Score (FCS). We then estimate the determinants of food security using general linear models. The food security metrics are not strongly correlated. For example, according to HFIAP, as many as 70 percent of households sampled are food insecure, but only 2 percent fall below acceptable thresholds measured by FCS. Model results show that household education, assets, and dwelling characteristics are significantly associated with food security according to HFIAS and HFIAP, but not with FCS. The poor correlation and weak model agreement between the dietary recall metric, FCS, and the experience-based metrics, HFIAS and HFIAP, call for closer attention to measurement of urban food security. Given Africa’s urban future, our findings highlight the need for an urban-oriented comprehensive approach to the food security of urban households.